Aspects of the ecology of fishes associated with salt marshes and adjacent habitats in a temperate South African estuary - Paterson, Angus William (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1999)
There is a paucity of published information on fish utilization of salt marshes outside North America. This dissertation represents the first intensive examination of the ichthyofauna associated with salt marshes in southern Africa and examines the species composition, diversity, size structure, distribution and estuarine dependence of fishes that utilize salt marshes in the Kariega Estuary. The research was concentrated on Taylor's salt marsh, with comparative studies being conducted on other salt marshes and habitats within the marine dominated Kariega Estuary. The possible importance of salt marshes as feeding and refuge areas for fishes was examined, as was the role of salt marshes in the food web of the estuary. The fishes frequenting salt marshes in the Kariega Estuary were predominantly the juveniles of marine species, with Mugilidae being the dominant family. The ichthyofauna was distributed primarily in the intertidal creeks with very few specimens captured on the vegetated Spartina maritima and Sarcocomia perennis flats. The different reaches of the intertidal creek were characterised by distinct fish assemblages. The fish assemblages associated with the intertidal salt marsh creeks were significantly different from those found in the eelgrass beds, the other dominant intertidal habitat in the Kariega Estuary. The eelgrass beds were dominated by estuarine fish species and had a higher density and standing stock of fishes when compared to the salt marsh creeks. The diversity of fishes in the two habitats was however similar. The intertidal salt marsh creek ichthyofauna also differed significantly from that found in the main estuary channel. The creek ichthyofauna was dominated by 0+ juveniles while the main channel had many subadult and adult fishes. The channel habitat also had numerous large piscivorous fishes which were absent from the salt marsh creeks. The low number of piscivorous fishes, together with limited fish predation from other sources, may be the reason why salt marshes provide a refuge for juvenile fishes that frequent these habitats. Unlike previous studies on North American, Australian and European salt marshes, the dominant fish species that frequented Taylor's marsh were not recorded feeding extensively on the marsh, and those that did had a limited distribution. The role of fishes in the transfer of energy off the Kariega salt marshes is therefore likely to be minimal. A stable carbon isotope study on the dominant primary producers and consumers within the Kariega Estuary revealed that detritus originating from the high lying salt marsh plants Sarcocornia perennis and Chenolea diffusa was not utilized by fishes in the Kariega Estuary. Preliminary results indicated that the cord grass Spartina maritima may be an important energy source to the fishes in the Kariega Estuary, but further research is needed to confirm this.
Keywords: Estuarine fishes -- Ecology -- South Africa; Salt marsh ecology -- South Africa